Chocolate Packaging and Purchase Behaviour: A Cluster Analysis Approach - Shekhar, Suraj Kushe; Raveendran, P. T. (Indian Journal of Marketing, 2013)
Packaging is regarded as an important component of our modern lifestyle, and a significant element of the branding process. Changing consumers’ lifestyle and increasing self-service has positioned product package as a tool to stimulate impulse buying and increase sales promotion. Chocolate is a product which is consumed irrespective of age barriers. Today, chocolate is marketed in different ways to different consumer segments and hence, packaging of chocolates is, therefore, critical. This study used a hierarchical cluster analysis approach to organize a group of 240 students into meaning clusters based on a combination of several independent chocolate packaging cues (cluster variables), which maximized the similarity of cases within each cluster while minimizing the dissimilarity between groups that were initially unknown. This was followed by one - way ANOVA to ascertain the significant differences between the groups on the classifying variables. Results reflected that cluster variables ("Price and purchase decision") were of paramount importance in purchase of chocolate bars. Cluster variables "Look for expiry dates," "Colour and purchase decision," and "Shape and purchase decision" were significant across all the three clusters. Variables like "Brand name and purchase decision," "Packaging material and purchase decision," "Picture and purchase decision," and "Size and purchase decision" were significant only for Clusters 1 and 2. "Look for ingredients," "Look for manufacturing unit’s address," and "Look for nutritional information" were significant for Clusters (1, 3) and (2, 3). Thus, the study scrutinized the key packaging cues influencing ’student clusters’.